Voice, Vulnerability, and Uneven Governance in Contemporary Asia: Editors’ Introduction - Asep Muhamad Iqbal (Journal of Asian Social Science Research, 2026)
This editors’ introduction presents the thematic scope and scholarly contributions of Journal of Asian Social Science Research, Volume 8, Number 1 (2026). Bringing together seven studies from Bangladesh, Afghanistan, Cambodia, India, and South Asia–Gulf contexts, the issue examines how power is negotiated through language, education, refugee governance, household relations, public health, local administration, diaspora networks, and development assistance. The articles converge around three themes: language as political and cultural action, institutionally structured vulnerability, and uneven local governance capacity. Using qualitative, mixed-source, and exploratory quantitative approaches, they connect regional transformations with everyday experiences of protest, exclusion, care, displacement, service provision, and livelihood insecurity. Collectively, the issue shows that social agency and resilience remain constrained when institutional authority, resources, participation, and protection are inadequate. It calls for comparative, empirically grounded research on voice, gendered governance, decentralisation, and development transition across Asia.